2010
DOI: 10.1177/1087054710370566
|View full text |Cite
|
Sign up to set email alerts
|

Are Maternal Genitourinary Infection and Pre-Eclampsia Associated With ADHD in School-Aged Children?

Abstract: Maternal GU infection appeared to be associated with increased risk of ADHD, and based on the findings it was concluded that further research is needed to describe the mechanism(s) underlying the association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
3
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 29 publications
8
91
3
2
Order By: Relevance
“…35,44,45 Our study contradicts some of these findings in that we found no association with acute events around delivery except for the rare event of cord prolapse in girls, also suggested in a recent study. 11 Maternal preeclampsia and genitourinary tract infections have been associated with other neurodevelopmental disorders, including ADHD, 12,46 where an inflammatory cascade affecting fetal brain development has been suggested. In our fully adjusted model, both preeclampsia and maternal genitourinary tract infections were associated with an elevated risk of ADHD irrespective of gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35,44,45 Our study contradicts some of these findings in that we found no association with acute events around delivery except for the rare event of cord prolapse in girls, also suggested in a recent study. 11 Maternal preeclampsia and genitourinary tract infections have been associated with other neurodevelopmental disorders, including ADHD, 12,46 where an inflammatory cascade affecting fetal brain development has been suggested. In our fully adjusted model, both preeclampsia and maternal genitourinary tract infections were associated with an elevated risk of ADHD irrespective of gender.…”
Section: Discussionmentioning
confidence: 99%
“…10 Others have suggested that the strong genetic risk for ADHD can be moderated or mediated by prenatal (eg, exposure to maternal stress, alcohol, nicotine, lead, preeclampsia, and maternal urinary tract infection [UTI]), perinatal (prematurity, low birth weight, anoxic-ischemic encephalopathy, meningitis, encephalitis), and postnatal (viral meningitis, encephalitis, cerebral trauma) factors. 6,8,9,11,12 However, population studies have shown varying results, from no elevated risk or low risk for ADHD due to perinatal factors 13,14 to an elevated risk associated with prematurity and postterm babies. 15,16 Recently there has been a focus on early term births (37-38 weeks' gestation), which may also increase the risk of ADHD.…”
mentioning
confidence: 99%
“…The relationship between exposure to prenatal maternal infection and the risk of ADHD has been examined in a study by Mann and McDermott [39]. The researchers focused on maternal genitourinary infection and pre-eclampsia and the offspring's risk of ADHD.…”
Section: Other Mental Disordersmentioning
confidence: 99%
“…Some studies [26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41] additionally collected exposure data by interviewing mothers during or shortly after pregnancy or using their medical records. Thereafter, several studies [42,43,44,45,46,47,48,49] used a more rigorous way of estimating maternal exposure by investigating prospectively collected maternal sera of offspring with psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Finalmente, Mann y cols., en informes independientes pero con los mismos pacientes seguidos para evaluar la asociación entre PE y parálisis cerebral, plantean que la PE también es un factor de riesgo para el trastorno de déficit de atención e hiperactividad (TDAH) 41 y las enfermedades del espectro autista (EA). 42 En el primer caso, encontraron que el 6,2% de los niños y niñas con diagnóstico de TDAH eran producto de embarazos con PE, frente al 5,5% de los otros 76 810 niños y niñas sin TDAH; el OR luego de ajustar por los factores de confusión fue de 1,19 (IC95% 1,07-1,32), siendo mayor si, además de la PE, la madre sufrió de cualquier infección genitourinaria durante la gestación (OR 1,53, IC95% 1,32-1,77).…”
Section: Trastornos Neurológicos Y De La Salud Mentalunclassified